Trichlorfon, a salmon lice pesticide, and the effect on metabolism and inflammation in Atlantic salmon (Salmo salar, L.) - Paulsen, Are Mæland (The University of Bergen, 2020)
Since the beginning of the salmon farming industry in Norway, the substantial fish health and welfare and economic costs caused by the parasitic salmon lice (Lepeophtheirus salmonis) has increased in tandem with the expanding production of salmon. In 1974, the first reported attempt at repelling the parasite was performed with the organophosphorus pesticide (OPP) trichlorfon (TCF). As L. salmonis established itself as one of the biggest biological challenges of commercial aquaculture industry, the quantitative use of pharmaceutical treatments used against salmon lice has escalated and proven to negatively affect both non-target species and the treated fish itself. In this study, isolated liver cells and head kidney (HK) leukocytes of 11 Atlantic salmon (Salmo salar, L.) post-smolts were exposed to TCF in concentrations of 25, 10 and 1 µM (1.3, 0.5 and 0.25 µL) for 48 hours and 100 µg/mL lipopolysaccharide (LPS) and 50 µg/mL polyinosinic:polycytidylic acid (poly I:C) for 24 hours in vitro, to examine the toxic effects of TCF and if it affects metabolic or immunogenic responses when under simulated bacterial (LPS) and viral (poly I:C) infection. Untreated cultures were included as controls. Transcription of the inflammatory markers CD83 and Cox-2 in isolated liver cells and HK leukocytes in addition to inflammatory markers IL-1β and TNF α in leukocytes, was significantly affected by LPS, further verifying the suitability of the in vitro model used in this experiment. Expression of the immunorelated metabolic genes was not significantly affected by any treatment. The gene expression of the oxidative stress (OS) related gene Bcl-2 was down regulated in leukocytes by poly I:C alone and poly I:C with TCF. Similarly, gene expression of the apoptotic related gene caspase3 was significantly upregulated in leukocytes cultured with poly I:C, suggesting an antiviral involvement. The expression of antiviral response genes Mx, significantly elevated in leukocytes by poly I:C, and viperin, significantly induced in both liver ...